Investigating the market structure for fish in Malaysia - Mohd. Arshad, Fatimah; Gibbons, E. T. (IDRC, 1987)
Fish marketing was comprehensively studied in Peninsular (or West) Malaysia during 1983-85. A simpler study has been designed to be carried out in Sri Lanka in 1986-87. The objectives, methodology conduct and findings of the Malaysia study are explained. A range of related issues, which did not arise directly from field research are discussed. To provide comprehensive profiles of key dimensions and characteristics at all level of particular marketing chains, a series of model-industry organization charts is proposed for future product-marketing studies. The proposed dimensions include volume produced, imported and exported; seasonal and lunar cycles; species mix; trade participants; prices; costs and margins; product usage; postharvest losses in volume and quality; and changes in the form of the products). Suggestions are offered concerning the design conduct, and control of studies of the marketing of fish and agricultural products in developing and developed countries.